Modeling of destruction processes of the installation connection of electronic equipment - Nevliudov, I.; Demska, N.; Starodubcev, N.; Nevliudova, V. (ХНУРЕ, 2019)
Modern technologies move away from the traditional design of hard electronics into the form factors of flexible switching structures, which are often operated in a dynamic mode and can be subjected to such actions as alternating loads, bending and twisting, stretching, vibration, the presence of a chemically aggressive environment, etc. Despite a large number of existing studies using an arsenal of achievements in the field of materials science, means of classical and quantum physics, the theory of chemical reactions, statistical physics, fracture mechanics, up to date, some essential phenomena occurring at the atomic-molecular level during the implementation of the manufacturing process and design of flexible structures have not been fully disclosed. In this paper, we consider the processes of the appearance in the materials and structures of connectors of products of physicochemical reactions associated with the presence of two sources of medium formation, which are interpreted as the formation in a certain place, over a certain period of time, of a substance with new properties, the appearance of which can cause degradation processes. As a result, the obtained dependences, together with the statistical processing of the obtained information, can provide a sufficient description of the process for its optimal control, even under conditions of incomplete certainty about the subtle mechanisms of atomic-molecular interaction between the materials involved in the process.